Quality of life is associated with fatigue among Brazilian professional dancers - Reis, Nycolle Martins (2019)
This cross-sectional study aimed to analyze the relationship between quality of life and levels of fatigue among Brazilian professional dancers. A total of 127 professional classical ballet and contemporary dancers, both male and female, from professional dance companies of the Brazilian South-Southeast region, participated in the study. Data were collected using online self-administered questionnaires, the World Health Organization Quality of Life – Biomedical Research and Education Foundation (WHOQOL – BREF) and the Fatigue Symptom Checklist (FSC), to characterize the participants. Multiple linear regressions were used for data analysis. The results showed that worsened psychological health, social relationships, environment, and total quality of life domains were associated with the drowsiness and dullness scale. Worsened physical health, psychological, and total quality of life domains were also associated with the inability to concentrate scale. However, improvement in social relationships and total quality of life domains were associated with the awareness of physical discomfort scale. These results indicate that fatigue affects the quality of life of professional dancers differently based on the scales used to measure fatigue, which highlights the importance of studies empirically testing specific fatigue-modifying factors in professional dance contexts.